Stories and Theatre for Teaching Physics at Primary School - Marco Giliberti (MDPI AG, 2021)
The paper contains progress reports supported by data about two short activities aimed at introducing physics themes in primary school. The first is a formal storytelling intervention named “Mommy Comet” carried out in first- and fifth-grade classes and concerning motion in the absence of forces in the Solar System broad context. The second is an informal work with third-, fourth- and fifth-degree students to investigate what physics is about. The results obtained by analyzing questionnaires and conducting interviews show how these narrative tools can offer wide potentialities and prove great effectiveness in introducing young students to physics.